APLIKASI E-WALLET: SOLUSI DIGITAL UNTUK PERLINDUNGAN HARTA BERDASARKAN MAQASID SYARIAH - Musanna, Khadijatul; Fitri, Aulia; Nabilah, Deva (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
E-wallet is an electronic media used to store electronic money through certain applications. Various services provided by the company make e-wallet more practical, fast, and efficient in transactions. The use of e-wallet can be evaluated in the context of hifz mal (preservation of assets) in maqashid sharia to ensure its compliance with sharia principles. Hifz Mal is an important part of Maqshid Sharia which aims for the benefit of the community in a legal case. Maqashid Sharia as the maintenance of goodness achieves benefits and prevents evil. All matters in Islam are global and specific, all can be solved based on public interest, this is in line with the concept of Maqashid Sharia. The research methodology used in this study is qualitative with content analysis techniques to obtain data. This study examines comprehensive articles and books related to e-wallet, as well as the views of scholars on the concept of hifz mal. The results of the study indicate that the use of e-wallet as an electronic transaction medium to purchase products or services is in accordance with the concept of hifz mal. The use of money stored in e-wallets as a means of exchange in digital transactions is widely accepted by the public and does not involve elements of usury, gharar, gambling, or exploitation. In addition, e-wallets offer high security features and dual benefits that can make people's lives easier, in accordance with the principle of maintaining assets in maqashid sharia.